Interrogating The Experiences Of The Girl Child In Internally Displaced Persons’ Camps In Benue State And What Faith-Based Organizations Can Do - UROKO, FAVOUR; Chibugo, Mrs Ugwu, Cynthia (Fakultas Filsafat Universitas Advent Indonesia, 2024)
The aim of this study is to examine the experiences of girls living in IDP camps in Benue State, Nigeria, and what FBOs could do to ameliorate their sufferings. The conflict in Benue State has occurred between the Fulani pastoralists, or herdsmen, and the indigenous people of Benue and it has led to the displacement of thousands of girls. Literature has not yet addressed the experiences of girls in internally displaced camps and the work of faith-based organisations in the various camps. Three camps in Benue State were chosen by the researchers. They are the Makurdi, Guma, and Agatu camps. Thirty (N = 30) in-depth interviews (IDI) with female IDPs in Benue State were conducted by the researchers. The participants were purposively selected. A semi-structured interview was adopted, and the data was analysed using content analysis. Emergent themes include the environment of the girl child in IDP camps, reasons for the abuse of the girl child in IDP camps, and impacts of the abuse on the girl child in IDP camps. Girls in Benue State's internally displaced people’s camps endure appalling living conditions, including little access to basic amenities, a high risk of sexual exploitation, and few options for employment and education.